Repair of Abdominal Wall with Homologous Duramater - Tellechea, Miguel; Zeballos, Javier; Vázquez, Daniel; Acosta y Lara, Armando; de Freitas, Luis; Bonaba, Roberto (Cirugía del Uruguay, 1979)
Analysis of viabiilty in use of homologous dura mater for closing abdominal gaps. It is easy to sterilyze, obtain and preserve, serving well its purpose of holding and isolating when placed between abdominal cavity and exterior. Satisfactory biological and surgical results were obtained in the 15 dogs studied.